Towards Green Lubrication in Machining - Liew Yun Hsien, Willey (Springer, 2015)
The book gives an overview of environmental friendly gaseous and vapour, refrigerated compressed gas, solid lubricant, mist lubrication, minimum quantity lubrication (MQL) and vegetable oils that can be used as lubricants and additives in industrial machining applications. This book introduces vegetable oils as viable and good alternative resources because of their environmental friendly, non-toxic and readily biodegradable nature. The effectiveness of various types of vegetables oils as lubricants and additives in reducing wear and friction is discussed in this book. Engineers and scientist working in the field of lubrication and machining will find this book useful.